The Legal Politics of the Aceh Governor's Policy Regarding Religious Activities in Public Sphere: David Easton's Political Theory perspective - Muhammad Fakhrul Mahdi; Ahmad Yani Anshori (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This article examines the phenomenon which caused the issuance and the formation of the Aceh Governor Circular Letter concerning the recitation prohibition other than the Aqidah of Ahlussunnah wal Jamaah. This article employs the empirical legal studies approach and the analysis of David Easton's system theory. This article finds that the Aceh Governor's Circular Letter was motivated by the emergence of the recitation phenomenon in the Aceh region, which teachings are considered apart from the Ahlussunnah wal Jamā'ah aqidah. This Circular Letter is also based on the existence of the Aceh Qanun Number 8 of 2014 demands and Aceh Ulema Consultative Council (MPU) support. The history of diversity, socio-religious practices, and education that developed in Aceh also contributed to the Aceh Governor Circular Letter promulgation. The Aceh Governor policy in David Easton's political theory is called the output sub-system (output). This policy has produced both positive and negative impacts. The negative impact of the Aceh Governor Circular Letter then becomes feedback for stakeholders to formulate new policies that could accommodate and protect all groups. Abstrak: Artikle ini mengkaji fenomena yang melatari lahirnya Surat Edaran Gubernur Aceh tentang larangan pengajian selain aqidah Ahlussunnah wal Jamaah beserta proses pembentukannya. Menggunakan pendekatan empirical legal studies dan analisis teori sistem David Easton diperoleh temuan sebagai berikut. Pertama, lahirnya Surat Edaran Gubernur Aceh dilatarbelakangi oleh munculnya fenomena pengajian di wilayah Aceh yang mengajarkan paham yang diyakini berada di luar aqidah Ahlussunnah wal Jamā'ah. Selain itu, ia juga didasarkan pada adanya tuntutan (demand) dari Qanun Aceh Nomor 8 Tahun 2014 serta dukungan dari Majelis Permusyawaratan Ulama (MPU) Aceh. Sejarah keberagamaan, praktik sosial keagamaan, dan pendidikan yang berkembang di Aceh juga ikut melatari lahirnya Surat Efaran Gubernur Aceh ini. Kedua, lahirnya kebijakan (policy) Gubernur Aceh tersebut dalam teori politik David Easton disebut sebagai subsistem keluaran (output). Kebijakan ini dalam faktanya telah melahirkan dampak positif dan negatif sekaligus. Dampak negatif dari Surat Edaran Gubernur Aceh tersebut kemudian menjadi umpan balik (feedback) bagi para pemangku kepentingan untuk merumuskan kebijakan baru yang bisa mengakomodasi dan melindungai semua kalangan.